Physical correlates of human-like softness elicit high tactile pleasantness - Kitada, Ryo (2021)
Touching an object can elicit affective sensations. Because these sensations are critical for social interaction, tactile preferences may be adapted to the characteristics of the human body. We have previously shown that compliance, a physical correlate of softness, increased the tactile pleasantness of a deformable surface. However, the extent to which object compliance similar to the human body elicits tactile pleasantness remains unknown. We addressed this question by using a wide range of compliances and by measuring the distribution of compliance of human body parts. The participants numerically estimated the perceived pleasantness or softness while pushing tactile stimuli with their right index fingers. The perceived softness monotonically increased with increasing compliance and then leveled off around the end of the stimulus range. By contrast, pleasantness showed an inverse U pattern as a function of compliance, reaching the maximum between 5 and 7 mm/N. This range of compliance was within that for both hand and arm. These results indicate that objects with similar compliance levels as those of human body parts yield the highest pleasantness when pushing them.